Obesity Is Not Associated with Impaired Immune Response to Influenza Vaccination in HIV-Infected Persons - Charitha Gowda; Noah McKittrick; Deborah Kim; Rosemarie A. Kappes; Vincent Lo Re; Pablo Tebas (AIDS Research and Treatment)
Introduction. HIV-infected individuals demonstrate lower immunogenicity to the influenza vaccine, despite immunologic and virologic control of HIV infection. Obesity has been previously shown to be associated with diminished antibody responses to other vaccines in HIV-uninfected persons. However, no studies have examined if obesity is associated with diminished protective immune response to influenza vaccination among HIV-infected persons on antiretroviral therapy (ART). Methods. We performed a retrospective analysis of immunogenicity data from a clinical trial of inactivated, trivalent influenza vaccine. The primary endpoint was the proportion of participants with seroconversion, defined as >4-fold increase in anti-hemagglutinin antibody titers after vaccination. Secondary endpoints were the proportion of participants with seroprotection (defined as antibody titers of ≥1 : 40) and geometric mean hemagglutination inhibition antibody titers. Results. Overall, 48 (27%) participants were obese (body mass index ≥ 30 kg/m2). Seroconversion rates were comparable between obese and nonobese subjects for all three vaccine strains. Further, postvaccination geometric mean titers did not differ by body mass index category. Conclusion. Obesity was not associated with diminished antibody response to influenza vaccination in a sample of healthy HIV-infected persons.